EDUKASI CINTA RUPIAH DALAM RANGKA MENCIPTAKAN MASYARAKAT PEDULI PEMBANGUNAN DI PASAR PASIA NAN TIGO KOTA PADANG - Yessy Andriani; Indrawari Indrawari; Laksmi Dewi (BULETIN ILMIAH NAGARI MEMBANGUN, 2020)
The high cost of printing money is a significant burden on the economy. The leading cause is the lack of public awareness in treating rupiah currency properly so that the money becomes easily damaged (not fit for circulation). If it is damaged, the money must be printed again. The more money is damaged, and the faster the damage occurs, the higher the cost of printing money. Traditional markets have significantly contributed to the acceleration of the destruction of money, especially wet markets such as fish markets. This activity aims to disseminate and educate fish traders about the importance of caring for and treating money well through the "Love Rupiah Movement." The love for rupiah movement is carried out by applying the 5J, namely Do not fold, do not cross, do not staple it, do not wet it, and do not squeeze it. This activity is located at the Pasie Nan Tigo Fish Market, Koto Tangah District, Padang City, after being successful in the previous Pasar Raya Padang. This activity was accompanied by a real act of love for rupiah by giving petty cases to 30 fish traders. The results obtained in this activity effectively increased participants' knowledge and understanding of the importance of protecting the rupiah currency and maintaining and caring for the rupiah currency properly. Thus this activity directly influences the behavior of many fish traders. This activity's direct impact was that fish traders began to implement the love of rupiah movement and use money storage boxes, so that rupiah currency was no longer wet. Their economic life would be longer. In the future, it is necessary to conduct more comprehensive socialization not only for fish traders but also for all traders to reduce the cost of printing money and save budget.